MENGURANGI TINGKAT KECELAKAAN PADA KAPAL RO-RO - SARINAH SARINAH; KHAIRUNAS KHAIRUNAS (Institut Transportasi dan Logistik Trisakti, 2015)
This study is aimed at finding out the effect of cargo supervision to the accident rate of KM. Madani Nusantara (Ro-ro/Passanger ship) route Balikpapan – Makassar – Pare-pare. The data analyses are regression, correlation, determinant coefficient and hypothesis test. The result showed that there is an effect of cargo supervision to the accident rate that can be proved using simple linear regression (Y = 7.45 + 0.79X). It means that each increasing point of variable X (cargo supervision) will affect variable Y (accident rate) which is 0.79 in 7.45 constants. Based on correlation analysis, r = 0.93 or +1 shows that there is a positive effect of cargo supervision to the accident rate. The determinant coefficient is 86.49 % proves that accident rate is most affected by cargo supervision while the rest (13.51 %) come from other factors such as cargo shipping documents and crew ship documents. The last result from hypothesis test is t count > t table or 36.43 > 1.701 which means there is a significant impact of cargo supervision to the accident rate of Ro-ro KM. Madani Nusantara.